2009
DOI: 10.5380/psi.v13i2.9799
|View full text |Cite
|
Sign up to set email alerts
|

Dificuldades ortográficas na escrita no ensino fundamental

Abstract: RESUMOO presente estudo teve por objetivo identificar o desempenho em escrita de crianças que frequentavam regularmente o ensino fundamental. Foi aplicada uma prova de escrita em 546 crianças, com faixa etária entre 7 e 13 anos, de ambos os sexos, que frequentavam 2ª e 3ª séries de escolas públicas e privadas do estado de São Paulo. Os resultados revelaram que os participantes da 3ª série apresentaram um desempenho melhor do que os da 2ª série, apesar de apresentarem pontuação máxima e mínima igual. A categori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
0
1
Order By: Relevance
“…This finding is observed despite the attempt to obtain a homogeneous sample as all students were referred by their teachers as having good academic performance. Furthermore, these results also support the majority of Brazilian studies that compare the writing of elementary school students which have found poorer performance of students belonging to Public Schools, even without learning complaints (7,9,11,18,22,23).…”
Section: Discussionsupporting
confidence: 75%
“…This finding is observed despite the attempt to obtain a homogeneous sample as all students were referred by their teachers as having good academic performance. Furthermore, these results also support the majority of Brazilian studies that compare the writing of elementary school students which have found poorer performance of students belonging to Public Schools, even without learning complaints (7,9,11,18,22,23).…”
Section: Discussionsupporting
confidence: 75%
“…The results of this study refute some research findings that suggest the school network, that is, public or private systems, as a factor interfering with academic performance as to spelling ability (3) , once there was no difference in mean of spelling errors among students at the fifth grade in GSPrS and GSPuS. Another study reported that schoolchildren at the fourth grade of private schools had less difficulty in writing compared with the students from public schools (16) , in agreement with our data when it comes to fourth grades in GSPrS and GSPuS.…”
Section: Discussioncontrasting
confidence: 64%